Development of fiberreinforced polypropylene with NaOH pretreated rice and coffee husks as fillers: Mechanical and thermal properties - Andrew Yiga, Vianney; Page, Sinja; Lubwama, Michael; Epple, Stefan; Olupot, Peter Wilberforce; Bonten, Christian (Journal of Thermoplastic Composite Materials, 2020)
Incorporation of agricultural wastes as fillers in fiber-reinforced plastics is gaining momentum in plastics engineering research. In this study, fiber-reinforced polypropylene (PP) with rice and coffee husks as filler material were developed. The effect of alkali (sodium hydroxide) pretreatment of the husks on mechanical and thermal properties of developed PP biocomposites was observed. Filler material loading was varied from 0% to 20% for rice husks and 0% to 10% for coffee husks. A twin-screw extruder was used for compounding the PP matrix with rice and coffee husk filler materials. Tensile strengths and percentage elongation results varied from 27.4 to 37.4 MPa and 2.4% to 70.3% (unmodified coffee husks), 31.1 to 37.4 MPa and 5% to 70.3% (unmodified rice husks), 30.7 to 37.4 MPa and 5.3% to 70.3% (modified coffee husks), and 30.7 to 37.4 MPa and 4.8% to 70.3% (modified rice husks). Young’s modulus ranged between 1656 and 2247.8 MPa for biocomposite PP samples with unmodified filler material. Young’s modulus ranged between 1740 and 2160 MPa after alkali treatment of the filler material. Charpy impact strengths ranged from 1.2 to 4 kJ/m2 and 3.1 to 19.6 kJ/m2 for samples containing unmodified and modified filler material, respectively. Thermogravimetric analysis showed that an increase in filler content resulted into delayed weight loss at high degradation temperatures. The results suggest that these developed fiber-reinforced plastics can be used in applications requiring high thermal stability and good mechanical properties.
Keywords: Alkali treatment; Cellulose; Coffee husks; Fiber-reinforced plastics; Polypropylene; Rice husks